1989
DOI: 10.1088/0953-8984/1/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic magnetic properties of the iron-rich ThMn12-structure alloys R(Fe11Ti); R=Y, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm and Lu

Abstract: Magnetic properties of the series of ThMn,,-structure intermetallic compounds R(Fe,,Ti) have been determined for rare earths from Nd to Lu plus Y. The highest Curie temperature (607 K) is for R = Gd, and R-Fe exchange interactions are much stronger for light rare earths than for heavy ones. The temperature dependence of the iron sublattice magnetisation and anisotropy are determined for the Y and Lu compounds. Spin reorientation transitions are found as a function of temperature for the rare earths with a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(65 citation statements)
references
References 33 publications
4
61
0
Order By: Relevance
“…Scanning electron microscope (SEM) and X-ray diffraction (XRD) analyses of the annealed sample show the compound was single phase. The lattice parameters obtained for the powder sample, a = 8.584 Å and c = 4.791 Å, are in good agreement with the literature [4].…”
Section: Experimental and Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Scanning electron microscope (SEM) and X-ray diffraction (XRD) analyses of the annealed sample show the compound was single phase. The lattice parameters obtained for the powder sample, a = 8.584 Å and c = 4.791 Å, are in good agreement with the literature [4].…”
Section: Experimental and Resultssupporting
confidence: 88%
“…Such observations are usually obtained from a precise magnetization measurements performed on single crystals. The peak shown in the magnetization curve of NdFe 11 Ti at 200 K [4] is thought to be due to a spin reorientation transition (SR) from conical to unixal anisotropy, but for a polycrystalline sample this temperature may be extended over a wide temperature range according to the sign of the second anisotropy constant (K 2 ) [4] (i.e. spin reorientation starts from a T SR1 , and completes at T SR2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The RFe 11 Ti intermetallic compounds are now reconsidered as promising materials for permanent magnets with low contents of rare earth materials. This compound has ThMn 12 -type tetragonal crystal structure (space group I4/mmm) and is characterized by reasonably high values of the Curie temperature and of the spontaneous magnetic moment [5][6][7]. DyFe 11 Ti compound has uniaxial magnetic anisotropy at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This compound is characterized by the two spin-reorientation phase transitions (SRT). According to the literature data, SRT temperatures significantly vary: the SRT1 is observed in the temperature range of 98-120 K, SRT2 -214-250 K [5][6][7][8][9][10]. Besides, DyFe 11 Ti compound possess the large magnetostriction [11].…”
Section: Introductionmentioning
confidence: 99%
“…1 The competing anisotropy contributions from the two sublattices can therefore lead to spin reorientation transitions. However, there exist some inconsistencies in the reported magnetic transitions for Dy(Fe,T) 12 compounds such as spin reorientation and first-order magnetization transition 4,5 -Hu et al 4 suggested that a first-order spin reorientation takes place at T sr1 with a second-order spin reorientation occurring at T sr2 , while Andreev et al 5 reported two consecutive second-order spin reorientations at T sr1 and T sr2 .…”
Section: Introductionmentioning
confidence: 99%